Analisis Penerapan Sistem Sanksi dalam Meningkatkan Kedisiplinan Pegawai Dinas Kepemudaan dan Keolahragaan Provinsi Sumatera Utara - Zainarti Zainarti; Ardhinur Ardhinur; Muhammad Fauzan Effendi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This study aims to analyze the application of the sanction system in improving the discipline of employees of the Department of Youth and Sports of North Sumatra Province. The method used is a qualitative method with data collection techniques through in-depth interviews with 10 employees who work at the Department of Youth and Sports of North Sumatra Province. The results showed that the application of the sanction system has succeeded in improving employee discipline, especially in terms of attendance and timely completion of tasks. However, there are still obstacles in applying sanctions to violations that are more complex and unclear rules. Therefore, it is recommended that the Department of Youth and Sports of North Sumatra Province improve and clarify the sanction system applied and provide training to employees about the consequences of disciplinary violations.